Fostering Cognitive Presence in Online Courses: A Systematic Review (2008-2020) - Robert L. Moore; Courtney N. Miller (Online Learning, 2022)
Within the Community of Inquiry (CoI) framework, cognitive presence has been central to success in higher education settings. This systematic review examined 24 articles published between 2008-2020 that empirically analyzed cognitive presence in online courses. We share the patterns that emerged regarding the interplay between teaching and cognitive presence and social and cognitive presence. We also explore how the four phases of cognitive presence—triggering event, exploration, integration, and resolution—were evident within specific instructional activities. We conclude with implications for practice that will be helpful for course instructors and designers seeking to foster greater cognitive presence within their online courses.